Teachers' perspectives on the implementation of alternative assessment in the classroom - Sulaiman, Tajularipin (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Assessment is an important instructional activity that provides information about the achievement of the intended learning outcomes. Assessment should be comprehensive and planned in order to evaluate the academic and character development of students in a holistic manner. The aims of this study are to identify the elements considered by teachers when assessing student progress, to examine the tendency of teachers to select forms of assessment and to determine teachers' understanding of the alternative assessment process. This study was conducted using a qualitative approach which involved interviews and document collection. A total of seven (7) teachers from different types of schools were randomly selected for this study. The respondents were divided into two groups; science and social science. The interview data were transcribed into verbatim form and analyzed using ATLAS.ti software. The findings indicate that teachers tend to develop questions based on Bloom's Taxonomy, guided by general knowledge and forming questions that require higher-order thinking. Teachers also combined formative and summative assessment to provide a more comprehensive assessment of the learning outcomes. Apart from that, the findings also showed that respondents understand that alternative assessment is an evaluation method using various techniques. They were also aware that questions in alternative assessment does not only focus on the content of the syllabus but also covers aspects of everyday life. In conclusion, alternative assessment can be seen as an approach that can play a role in enhancing the development of individuals to be more critical, productive and innovative.